Outcome of Congenital Cytomegalovirus Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The long-term neurodevelopmental outcome in 41 children with symptomatic congenital cytomegalovirus (CMV) infection was studied by investigators at Baylor College of Medicine and the Houston CMV Study Group.